Binaural summation in normals and sensorineural hearing loss - Singh, S. Venugopal; Harjeet (Journal of All India Institute of Speech and Hearing)
Binaural summation was tested in fifteen normal hearing adults and fifteen subjects with bilateral symmetrical SN loss for 500 Hz & 200 Hz puretones and wideband noise of 500 m sec. duration at O dBSL, 20 dBSL & 40 dBSL. Results indicated thai SN loss group showed significantly less summation than normals and there was a non-linear increase in summation with increasing frequency and intensity in both groups. A few theoretical explanations and recommendations are suggested.